Transformation of the digital technologies ecosystem in the supply chains of trade enterprises in Montenegro - Crvenica Dejana; Somborac Borko; Stevanović Mirjana; Vujičić Slađana; Ranisavljević Mihajlo (Ekonomija: teorija i praksa)
Logistic systems are increasingly recognized as key drivers of economic growth in society. The market's demand for delivery efficiency has forced organizations to continually improve their logistics systems. The development of global competitiveness requires the transformation of digital technologies in trade enterprises in Montenegro. As an emerging economy, Montenegro's economic growth is based on increasing entrepreneurial activity and the ability to adopt digital technologies that enable smoother flows of information, services, and products. This paper examines the current use of various digital technologies in organizations closely connected to logistics functions. The results will indicate the extent to which technological innovations have been implemented in trade enterprises in Montenegro, along with opportunities for further development of these functions. By defining the null and alternative hypotheses and analyzing the results, this paper will provide a clear overview of the capabilities of organizations in Montenegro to effectively manage modern technological processes in logistics.